10-kHz-rate two-color dual-plane stereo-PIV using an optical parametric oscillator. (1st May 2023) - Jiang, Naibo; Hsu, Paul S; Fugger, Christopher A; Schmidheiser, Sara E; Emerson, Benjamin L; Lieuwen, Timothy C; Roy, Sukesh
Abstract: 10 kHz-rate dual-plane stereoscopic particle-image velocimetry (DSPIV) was applied in a swirling jet flame measurement simultaneously with hydroxyl planar laser-induced fluorescence (OH-PLIF). A high-speed burst-mode laser system with an optical parametric oscillator were used in double-pulse laser generation of 532 nm for one plane and 607 nm for the second plane. Temporally-resolved particle image velocimetry (PIV) image sequences, nine-component velocity gradient tensor, and simultaneous OH-PLIF images are presented. Flow vorticities and strain rates are also obtained with the measured velocity gradients. Compared with previous polarization-based dual-plane PIV technique, two-color based DSPIV measurement has distinctive advantages in elimination of signal interference from different PIV plane due to polarization leakage and hence improves measurement accuracy.